Comportamiento de indicadores reproductivos individuales. I. Novillascriollas de Cuba - Javier de Loyola Oriyés, Carlos; Carlos Oliva Díaz, Roberto Ca; Ramírez Oriyés, José A.; Garay Durba, Magaly (apm, 2025)
NOTA TÉCNICA